MOBILISATION STRATEGIES AND PROJECT PARTNERSHIP AS PREDICTORS OF SUSTAINABLE SELF-HELP PROJECTS IN SOUTHWESTERN NIGERIA (2012)
Research evidence shows there is a dire need for the involvement and participation of people in every stage of self- help project lifecycle to ensure sustainability. In order to achieve this, emphasis should be placed on effective mobilisation strategies. Though there is vast literature on citizen mobilisation and participation in community development, there is little emphasis on the effectiveness of the actual mobilisation strategies adopted and the extent to which the local community people partner with other stakeholders at each stage of self-help project lifecycle. This study, therefore, examined the extent to which mobilisation strategies (Development information network, community education, popular theatre and age grade) and project partnership (initiation, planning and designing, funding, execution, monitoring and evaluation) predict sustainability of self-help projects in Oyo, Ogun and Ondo states of Southwestern Nigeria. The survey research design of the ex-post facto type was adopted. One thousand, two hundred and seventeen respondents were selected using proportional stratified random sampling technique. These comprise Political / Opinion leaders, 326; Religious leaders, 241; Youth leaders, 270; Non-governmental organisation officials, 102; Community members, 152 and Change-agents, 126. Three instruments: Mobilisation Strategies Scale, r=0.84; Project’s Partnership Scale, r=0.78; and Self- help Project’s Sustainability Scale, r=0.82; were used. These were complemented with six sessions each of Focus Group Discussions and Key Informant Interviews. Three research questions were answered and two hypotheses tested at the 0.05 level of significance. Data were analysed using descriptive statistics and multiple regression while content analysis was used for the qualitative data. Mobilisation strategies and project partnership significantly correlated, R=.402 with sustainability of self- help projects (F (5, 1211) = 29.957; p< 0.05) and with mobilisation strategies recording the highest contribution. They jointly accounted for 16% to the variance of the dependent measure. Relatively, mobilisation strategies contributed as follows: Development information network (β = .244); community education (β = .157); popular theatre (β = -.108); and age grade (β = .090). While project partnership factors ranked in the following order: project initiation (β =0.407; t=13.804 P<0.05); planning and designing (β=0.143; t=4.998; P<0.05); funding (β =-.290; t=-9.018; P<0.05); execution (β=-5.593E-02; t=-2.616; P<0.05); monitoring and evaluation (β=0.108; t=5.807; P<0.05). Further, the results revealed that mobilisation strategies were adopted for use as ranked: Development information network (β=25.13); Community education (β=23.29); Popular theatre (β =33.13); and Age grade (β=29.84). The Qualitative findings further showed that participants believed the usage of appropriate mobilisation strategy and maximum cooperation with development partners were essential ingredients for self- help project’s sustainability and that, project initiation was the joint effort of community developers; community people were empowered through acquisition of skills; effective provision of development information helped in sharing of ideas. Development information network, community education, popular theatre and age grade were effective mobilisation strategies for enhancing optimum citizen participation in all stages of projects’ life cycle. Therefore, developmental planners should give priority to elements of mobilisation strategies that could bring about full involvement and cooperation of the local community in every stage of projects in Southwestern Nigeria.